Endothelial–Vascular Smooth Muscle Cells Interactions in Atherosclerosis - Li, Manna; Qian, Ming; Kyler, Kathy; Xu, Jian (Frontiers in Cardiovascular Medicine, 2018)
Atherosclerosis is a chronic progressive inflammatory process that can eventually lead to cardiovascular disease (CVD). Despite available treatment, the prevalence of atherosclerotic CVD, which becomes the leading cause of death worldwide, persists. Identification of new mechanisms of atherogenesis are highly needed in order to develop an effective therapeutic treatment. The blood vessels contain two primary major cell types: endothelial cells (EC) and vascular smooth muscle cells (VSMC). Each of these performs an essential function in sustaining vascular homeostasis. EC-VSMC communication is essential not only to development, but also to the homeostasis of mature blood vessels. Aberrant EC-VSMC interaction could promote atherogenesis. Identification of the mode of EC-VSMC crosstalk that regulates vascular functionality and sustains homeostasis may offer strategic insights for prevention and treatment of atherosclerotic CVD. Here we will review the molecular mechanisms underlying the interplay between EC and VSMC that could contribute to atherosclerosis. We also highlight open questions for future research directions.